2024
DOI: 10.3390/math12030389
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Current Transformer Saturation Based on Machine Learning

Ismoil Odinaev,
Andrey Pazderin,
Murodbek Safaraliev
et al.

Abstract: One of the tasks in the operation of electric power systems is the correct functioning of the protection system and emergency automation algorithms. Instrument voltage and current transformers, operating in accordance with the laws of electromagnetism, are most often used for information support of the protection system and emergency automation algorithms. Magnetic core saturation of the specified current transformers can occur during faults. As a result, the correct functioning of the protection system and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recognizing this limitation, numerous studies have focused on extracting knowledge from artificial neural networks and developing explanatory techniques to provide insights into the network's behavior in particular situations [15,27]. Hence, it should be observed that each time the network undergoes retraining, a distinct value will be obtained [13,27]. Figure 5 presents the flowchart of the PRN network used to classify the operating conditions of a power transformer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing this limitation, numerous studies have focused on extracting knowledge from artificial neural networks and developing explanatory techniques to provide insights into the network's behavior in particular situations [15,27]. Hence, it should be observed that each time the network undergoes retraining, a distinct value will be obtained [13,27]. Figure 5 presents the flowchart of the PRN network used to classify the operating conditions of a power transformer.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental findings demonstrate that the proposed approach achieves a high level of classification accuracy and provides precise health assessments for power transformers. Topics related to the application of artificial neural networks (ANNs) in the analysis of the operating conditions of power transformers and electrical energy systems have currently received attention [13][14][15]. In recent years, a series of studies and research have been published in this field, demonstrating the growing interest and relevance of these approaches [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%